PsycEXTRA Dataset 2014
DOI: 10.1037/e573552014-059
|View full text |Cite
|
Sign up to set email alerts
|

Does incidental disgust amplify moral judgment? A meta-analytic review of experimental evidence

Abstract: The role of emotion in moral judgment is currently a topic of much debate in moral psychology. One specific claim made by many researchers is that irrelevant feelings of disgust can amplify the severity of moral condemnation. Numerous studies have found this effect, but there have also been several published failures to replicate this effect. Clarifying this issue would inform important theoretical debates between rival accounts of moral judgment. We meta-analyzed all available studies, published and unpublish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
115
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(125 citation statements)
references
References 21 publications
9
115
1
Order By: Relevance
“…With failed replications on various topics getting published these days, we were pleased that Landy and Goodwin's (2015, this issue) meta-analysis supported most of the findings we reported in Schnall, Haidt, Clore, and Jordan (2008). They focused on what Pizarro, Inbar and Helion (2011) had termed the amplification hypothesis of Haidt's (2001) social intuitionist model of moral judgment, namely that "disgust amplifies moral evaluations-it makes wrong things seem even more wrong (Pizarro et al, 2011, p. 267, emphasis in original)."…”
supporting
confidence: 64%
See 1 more Smart Citation
“…With failed replications on various topics getting published these days, we were pleased that Landy and Goodwin's (2015, this issue) meta-analysis supported most of the findings we reported in Schnall, Haidt, Clore, and Jordan (2008). They focused on what Pizarro, Inbar and Helion (2011) had termed the amplification hypothesis of Haidt's (2001) social intuitionist model of moral judgment, namely that "disgust amplifies moral evaluations-it makes wrong things seem even more wrong (Pizarro et al, 2011, p. 267, emphasis in original)."…”
supporting
confidence: 64%
“…They focused on what Pizarro, Inbar and Helion (2011) had termed the amplification hypothesis of Haidt's (2001) social intuitionist model of moral judgment, namely that "disgust amplifies moral evaluations-it makes wrong things seem even more wrong (Pizarro et al, 2011, p. 267, emphasis in original)." Like us, Landy and Goodwin (2015) found that the overall effect of incidental disgust on moral judgment is usually small or zero when ignoring relevant moderator variables. Like us, they found that there appears to be something special about olfactory inductions-they often work even without requiring moderators.…”
mentioning
confidence: 92%
“…Most notably, researchers investigating changes in moral judgment have tended to make a distinction between moralization and moral amplification. According to this distinction, something would be considered moralization if a morally neutral act enters the moral sphere, while a shift from seeing a slightly wrong act as more wrong would be considered moral amplification (Avramova & Inbar, ; Landy & Goodwin, ; Pizarro, Inbar, & Helion, ).…”
Section: Revisiting Rozin's Definitionmentioning
confidence: 99%
“…Despite the initial promise of incidental affect accounts, there has been very little subsequent work clearly demonstrating moral recognition following an incidental affect induction. In a recent meta‐analysis conducted by Landy and Goodwin (), it was found that incidental affect inductions did appear to have a small but significant effect on moral recognition ( d = .21, p = .01, 95% CI [.05, .37]). However, the interpretation of this effect size was limited by the small number of studies ( k = 13).…”
Section: Revisiting Rozin's Definitionmentioning
confidence: 99%
“…Moral perceptions also change based on temporary mood. Incidental inductions of disgust from dirty desks or fart spray have been associated with harsher moral judgments (Schnall, Haidt, Clore, & Jordan, ; Van Dillen, van der Wal, & van den Bos, ; but see Landy & Goodwin, ), likely because of the negative affect (Valdesolo & DeSteno, ) and perceived harm (Gray & Schein, forthcoming; Schein et al, forthcoming) inherent in disgust. Whereas moral psychologists once asked if emotions play a role in moral cognitions, they now ask how emotions play a role.…”
Section: Variabilitymentioning
confidence: 99%